Risk‐neutral skewness and commodity futures pricing. Issue 4 (14th January 2022) - Fuertes, Ana‐Maria; Liu, Zhenya; Tang, Weiqing
Abstract: This paper investigates the predictive content of risk‐neutral skewness (RNSK) for the dynamics of commodity futures prices. A trading strategy that buys futures with positive RNSK and sells futures with negative RNSK generates a significant excess return. Unlike traditional commodity risk factors' signals, the positive return generated from the RNSK signal is more pronounced in the contango phase. After controlling traditional commodity risk factors, the RNSK signal exhibits a more stable and prolonged predictive ability. The directional‐learning hypothesis explains the RNSK impact when commodity futures show higher idiosyncratic risks and illiquidity (positive RNSK) and overpriced (negative RNSK).